Study of body composition and motor competence in children from the 1st basic cycle and their relationship with school performance - Miguel Rebelo; Samuel Honório; António Pais; Jorge Santos; Paulo Afonso; Catarina Marques; Afonso Diniz; João Serrano (BMC Pediatrics)
Abstract Childhood obesity is a public health problem that affects many parts of the world, and is one of the factors that has negatively influenced levels of motor competence at an early age. However, these relationships remain poorly investigated. The aim of this study was to assess body composition (BC) and motor competence (MC), as well as to study their relationship with school performance in primary school children in Portugal. A quantitative study was carried out with a sample of 272 children aged between 6 and 10 years old, divided into 4 years of schooling. The Motor Competence Assessment was used to assess motor competence (MC) and a bioimpedance scale (InBody) was used to assess body composition (BC). The results showed that, with the exception of 1st year, all the children were overweight and this worsened as the school year progressed. As for motor competence, it increases as the children grow, but at low levels for their age, with only the 3rd and 4th years showing a relationship between MC and BC. The results also showed a positive relationship between academic achievement and MC only in the 4th year of schooling. These results highlight the need for intervention in primary schools to combat childhood obesity and motor illiteracy, as well as demonstrating that the better children’s MC, the better their school performance.